IMPLEMENTASI KEBIJAKAN PEMERINTAH KABUPATEN LOMBOK BARAT DALAM PENGGUNAAN PRODUK LOKAL UNGGULAN DAERAH - Lalu Bagus Prihatin Pujasetiandi; Diswandi Diswandi; Luluk Fadliyanti (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2020)
This study aims to examine the implementation of the West Lombok Regent Circular on Circulation, Use of Iodized Salt in West Lombok Regency. The method used is descriptive qualitative associated with the policy theory of George C. Edwards III, Marilee S. Grindle, and Donald S. Van Meter and Carl E. Van Horn using 9 variables. The results showed the Regent's Circular was implemented by involving the Bina Laut Sharia Cooperative. In general, SKPDs adhere to the Regent's Circular, but there are some SKPDs that do not routinely buy salt. There are two factors that become obstacles, namely Communication and Human Resources. With the Circular, salt marketing becomes more secure, thereby increasing the income and welfare of salt farmers and administrators of the Bina Laut Sharia Cooperative. At the same time answering the results of previous research by Khaerunnisah (2016), said that the main obstacles faced by salt farmers in the District of Sekotong are salt prices are still low and marketing is not smooth.